A transatlantic divide? The US and EU's approach to the international regulation of intellectual property trade-related agreements - Meir Perez Pugatch (European Centre for International Political Economy (ECIPE), 2007)
The TRIPs plus phenomenon (additional steps to strengthen the Agreement on Trade-Related Aspects of Intellectual Property Rights) tends to be attributed to the regional and bilateral efforts of the United States. This paper suggests that such a perception is mistaken. The EU certainly seeks to secure TRIPs plus provisions with its negotiating partners. However, the paper also suggests that, compared to the United States, the EU's approach towards the international regulation of IPRs is less effective and does not fully meet the EU's objectives in this field. The United States employs a more "hands-on" strategy at the regional and bilateral level, while the EU's tendency to incorporate international conventions and treaties into its regional and bilateral agreements suggests that it still favours the multilateral approach. But the European Commission seems to become more proactive in the international regulation and enforcement of IPRs and should coordinate its efforts with the United States.
Keywords: F13; F14; F19; F21; F53; 330; Trade Policy; Free Trade Agreements; Intellectual Property Rights; International Policy Coordination